2007
DOI: 10.1021/jo7013609
|View full text |Cite
|
Sign up to set email alerts
|

Summation of Nucleus Independent Chemical Shifts as a Measure of Aromaticity

Abstract: When the nucleus independent chemical shifts, NICS(1)zz, for a set of aromatic and antiaromatic hydrocarbons are summed, they show an excellent linear relationship with the magnetic susceptibility exaltation, Lambda, for neutral, cationic, and monoanionic species. Aromatic and antiaromatic dianions show a similar relationship but with a different slope. However, when both Lambda and the summation of NICS(1)zz are divided by the area of the ring squared, the vast majority of the aromatic and antiaromatic specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
99
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(107 citation statements)
references
References 53 publications
8
99
0
Order By: Relevance
“…23 The good linearity also allowed us to demonstrate that the sum of the NICS values for each individual ring in a polycyclic system is an effective measure of the aromaticity of the system as a whole. This study also showed the value of using a combination of aromatic and antiaromatic species because the greater range of values obtained with the inclusion of antiaromatic species gave a more convincing demonstration of linearity.…”
Section: Do Et Almentioning
confidence: 81%
See 3 more Smart Citations
“…23 The good linearity also allowed us to demonstrate that the sum of the NICS values for each individual ring in a polycyclic system is an effective measure of the aromaticity of the system as a whole. This study also showed the value of using a combination of aromatic and antiaromatic species because the greater range of values obtained with the inclusion of antiaromatic species gave a more convincing demonstration of linearity.…”
Section: Do Et Almentioning
confidence: 81%
“…22 The NICS(1) zz values are reported for the individual ring systems as well as for the summation of the three rings in the fluorenyl system (Tables 3 and 4). 23 The dihedral angles of the phenyl rings of 1 2þ and 2 2þ are approximately 50°; those for the phenyl rings of 3 2þ and 4 2þ are approximately 60°( see the Supporting Information). Because the top and bottom sides of the fluorenyl systems are not exactly the same, there is a slight difference in the magnitude of the NICS values.…”
Section: Evaluation Of Antiaromaticity Through Magnetic Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…However, to place these values in a larger context by comparison with other aromatic and antiaromatic species, each value needs to be normalized by the square area of the ring system. We have demonstrated a linear relationship between the ΣNICS(1) zz /sq area and Λ/sq area, 22 and that relationship is shown in Figure 1, 23 The plot also includes planar (D 4h ) cyclooctatetraene, which is presumed to be the transition state for inversion of the tub-shaped geometry of cyclooctatetraene. 24 Attempted Preparation of 1a 2À À1f 2À through Reduction with Lithium or Potassium.…”
Section: Introductionmentioning
confidence: 87%